(untitled) (Global Journal of Management and Business Research, 2017)
In the light of recent theoretical and empirical work, this article analyzes the role of institutional adaptation on the attractiveness of CEMAC countries for FDI. The aim is to ascertain whether the most commonly tested institutional determinants play an attractive role in the CEMAC zone. More specifically, we try to evaluate first the importance of the role played by capital market on the attraction of FDI and, secondly, measure the relative importance of the role played by politico-sociocultural capital in Countries of the CEMAC. The institutional approach is then the theoretical foundation of our analysis. In order to account for the performance of the theory of institutional adaptation, we examine it in an econometric regression analysis of panel data. An equation of the determinants of the attractiveness of the CEMAC countries with regard to FDI is estimated by the generalized method of moments (GMM) in dynamic panel for the period from 1985 to 2015. At the end of this analysis, we obtained the results which confirm our initial hypothesis that the attractiveness of the CEMAC countries is explained more by market capital than by political-sociocultural capital.